APPLICATION OF THE THEORY OF LATENT VARIABLES TO PERSONNEL MANAGEMENT METHODS - Averina, Tatiana; Barkalov, Sergey; Moiseev, Sergey (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
One of the main tasks of the human-resources (HR) department is the qualitative management of personnel, which is the basis for effective work of the organization. The paper presents models of personnel management based on the theory of latent variables. Research objective is to use the Rasch model for assessing latent variables to evaluate the competence of employees and  their suitability for certain positions and also quality control of their work.Three problems of personnel management are considered.Organization of qualitative selection of candidates for vacancies by objective assessment of the degree of professional suitability of candidates with a view to selecting the best employees. Multilateral monitoring as the quality of performance of duties of each employee on the one hand, and the efficiency of the work of the whole team on the other. A dynamic comparison is made between the quality of performance of their duties in different periods of time. Effective appointments of specific employees to certain positions. Based on the criteria of the employee's suitability for certain positions, the integral degree of the employee's suitability for each vacancy is calculated. In addition, the model makes it possible to assess the degree of influence of the criteria on the evaluation of employees.The models proposed in the paper allow obtaining estimates on a linear interval scale, which can be translated into any other scale, for example, probabilistic. Estimates do not depend on a set of criteria and the set of evaluated employees.